Surfactant tunable hierarchical nanostructures of CdIn2S4 and their photohydrogen production under solar light - Bhirud, Ashwini P.; Chaudhari, Nilima; Nikam, Latesh; Sonawane, Ravindra; Patil, Kashinath; Baeg, Jin-Ook; Kale, Bharat (International Journal of Hydrogen Energy, 2011)
The hierarchical nanostructures of CdIn2S4 were selectively prepared through hydrothermal process in the presence of different surfactants. Structural study demonstrated existence of cubic spinel structure and micro structural study shown a pretty marigold flower like morphology without any surfactant. The effect of surfactants on the morphology and microstructure of CdIn2S4 has been studied by using Polyvinyl pyrrolidone (PVP) and Cetyltrimethyl ammonium bromide (CTAB) as a surfactants. The CdIn2S4 bipyramids with length of 0.7-1 mu m have been obtained using PVP. Interestingly, the nanopetals (thin and transparent) of CdIn2S4 are self assembled into hollow spheres in the presence of CTAB. Considering the importance of these unique nanostructures, the growth mechanism has also been proposed. The optical properties demonstrated the band gap in the range of 2.12-2.29 eV which is well within the visible region. In this contest, photocatalytic activity for hydrogen production using the above nanostructures under visible light was also demonstrated. The prima-fascia observations shows that the bipyramidal CdIn2S4 exhibit excellent photocatalytic activity for hydrogen production (3238 mu molh(-1)) than other nanostructures. Being a nanostructured semiconductor chalcogenide with a good stability will also have potential applications in solar cells and LED. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Bipyramids; CdIn2S4; Hydrogen generation; hydrothermal; Self-assembled

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation

Magnetic alignment of gamma (core)-alpha (shell) Fe2O3 nanorods in a solid polymer electrolyte for Li-Ion batteries - Schaetzl, Dean M.; Li, Peng; Chaudhari, Nilima; Bernstein, Gary H.; Fullerton-Shirey, Susan K. (Journal of Physical Chemistry C, 2014)
The temperature-dependent ionic conductivity and thermal properties are characterized for a solid polymer electrolyte of poly(ethylene oxide) (PEO) and LiClO4 filled with 1 wt % gamma-phase core (maghemite) and alpha-phase shell (hematite) Fe2O3 nanorods. Samples are solvent-cast in the absence and presence of a 0.5 T magnetic field, dried at room temperature under vacuum for 72 h, and measured under nitrogen. Vibrating sample magnetometry indicates that the magnetic treatment aligns the nanorods to some extent in the desired orientation normal to the electrode surface. For samples with an ether oxygen to lithium ratio (EO/Li) of 10:1, the nanorods induce sample-to-sample variability in the ionic conductivity. The magnetic treatment eliminates this variability, and differential scanning calorimetry data support the observation that the magnetic treatment increases the structural homogeneity of the electrolyte. For samples with an EO/Li of 3:1, the ionic conductivity is 3 orders of magnitude larger for samples containing 5 times more of the crystal structure, (PEO)(6)/LiClO4. This result is surprising because an inverse relationship between crystallinity and conductivity is normally observed for semicrystalline, solid polymer electrolytes. When the crystal fraction is increased by a factor of 8 via the combination of nanorods and magnetic treatment, the conductivity does not continue to increase, showing that the effect does not persist beyond a critical fraction of (PEO)(6)/LiClO4. The results demonstrate that field-effect alignment of magnetic nanorods increases the crystal fraction and homogeneity of PEO/LiClO4, but does not affect the ionic conductivity in the range of salt and nanorod concentrations investigated.